Negotiating between Integrative Pesantren Models and Entrepreneurial Approaches in the Transformation of Islamic Higher Education Institutions - Sholikah, Sholikah; Amin, Fathul; Aziz, Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study examines how two Islamic higher education institutions in Tuban. IAINU Tuban with its entrepreneurial campus orientation and IAI Al-Hikmah Tuban with its integrative pesantren model—manage institutional transformation. Employing Schneider and Beatty’s institutional transformation framework and a qualitative multi-site design, data were obtained from the rectors and vice-rectors of both campuses through in-depth interviews, document analysis (including statutes, RIP, strategic plans, operational plans, and field notes), and direct observation. The data were processed using content analysis, presentation, and conclusion drawing, supported by triangulation of sources and techniques to ensure credibility. Interviews were conducted with campus leaders, the rector, and the vice-rector, as well as observations at the university during the same academic year. Data were analyzed using qualitative methods validated through triangulation of sources and techniques, then interpreted based on selected theories. The findings suggest that the negotiation between entrepreneurial orientation and pesantren integration does not create a zero-sum competition but rather a complementary dynamic. IAINU Tuban emphasizes market orientation, entrepreneurship training, and industry partnerships, while IAI Al-Hikmah Tuban prioritizes pesantren-based character education and community engagement. Both institutions demonstrate adaptive strategies shaped by local traditions and global challenges, resulting in hybrid institutional models. This study makes a theoretical contribution by enriching the literature on institutional transformation in Islamic higher education through a negotiation lens, while also providing practical implications for policymakers and university leaders in balancing modern competitiveness and Islamic values. This research offers a conceptual contribution in the form of an Islamic Hybrid Institutional Model relevant to the development of Islamic institutional transformation theory. Empirically, this study enriches the literature with a contextual portrait of the transformation of two Islamic universities in Tuban, IAINU Tuban and IAI Al-Hikmah Tuban which demonstrates how pesantren values and entrepreneurial orientation can productively negotiate.